Implementación de un sistema de control para el bombeo de agua de regadío en la comunidad Cruz Loma, cantón Latacunga, provincia de Cotopaxi - De la Cruz De la Cruz, Diego Armando (2022)
The technological proposal had as aim to implement a control system for the irrigation water pumping to supply the inhabitants from Cruz Loma community, located in the Latacunga canton, it is a field and experimental research, it is to determine the impact that caused by this type of problem within the society and through the experimental method it was made a comparison series to determine if the proposed hypothesis is accepted or rejected the study variable is the control system. The population was constituted by the inhabitants, who make up the aforementioned community, the same one that consists of 125 partners, what belong to the Irrigation Water Board, the used instruments for the system development and implementation were quantitative measurement technological devices for the measurement and getting data, by collection these data, by it could perform the assessment of pumping system, in order to verify, if the system will be optimal, the got results from the implementation were processed, through the tables and graphs use to visualize the electrical and hydraulic system behavior, as a result, it was got a 16.51 m^3/h flow, the reached maximum pressure is 70 Psi, in the electrical system, it was implemented an SSW-05 soft starter with a 60 A current, the purpose is to achieve a gradual start to avoid overcurrents, overloads, network harmonic distortion and protect both the transformer and or to the centrifugal pump. The maximum nominal current, operating at full load is 39.8 A and the voltage is 208V, in the control system, through programming in the PLC, with the implemented level sensors, it can be controlled the liquid level, optimally, it is established, what the system operating under normal conditions.